The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/ajhb.23328
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural wealth better predicts mental wellbeing than market wealth among highly vulnerable households in Haiti: Evidence for the benefits of a multidimensional approach to poverty

Abstract: Objectives Lack of wealth (poverty) impacts almost every aspect of human biology. Accordingly, many studies include its assessment. In almost all cases, approaches to assessing poverty are based on lack of success within cash economies (eg, lack of income, employment). However, this operationalization deflects attention from alternative forms of poverty that may have the most substantial influence on human wellbeing. We test how a multidimensional measure of poverty that considers agricultural assets expands t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 95 publications
1
17
1
Order By: Relevance
“…In addition to disparities in growth and nutrition, the AWI index may be useful in understanding other important demographic and health differences (Hadley, Maxfield, and Hruschka 2019; Lachaud et al. 2019). For example, the AWI may provide insights into the patterns of fertility change in many low‐ and middle‐income countries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to disparities in growth and nutrition, the AWI index may be useful in understanding other important demographic and health differences (Hadley, Maxfield, and Hruschka 2019; Lachaud et al. 2019). For example, the AWI may provide insights into the patterns of fertility change in many low‐ and middle‐income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Wealth indices that prioritize assets accrued through cash-based transactions can mask important sources of economic capacity and neglect crucial distinctions between individuals and households engaged in livelihoods outside of the cash economy. For example, a recent study of mental health in Haiti showed that a wealth index capturing agricultural success showed stronger associations with reduced anxiety and depressive symptoms than did a wealth index that captured success in the cash economy (Lachaud et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations